An empirical study into the relationship between voluntary disclosures and cost of equity capital for companies in the manufacturing industry listed on the SGX mainboard and SESDAQ. - Ho, Chan Fei. (2008)
This study attempts to validate the claim that lower cost of equity capital is an important benefit of increased voluntary disclosure by examining the association between voluntary disclosure and the cost of equity capital.